A Comparative Analysis of Learner Profiling and Role-Playing Approaches for Personalized English Sessions in Multi-Linguistic Milieus - Chemistry, Valerie Indiana; Najah, Salwa Maziyatun; Krisyati, Nety (FKIP Universitas Lampung, 2024)
A Comparative Analysis of Learner Profiling and Role-Playing Approaches for Personalized English Sessions in Multi-Linguistic Milieus. Objective: Despite meeting formal English reading and writing standards, Indonesian students face significant challenges in developing practical speaking skills due to limited daily English exposure and multiple linguistic barriers from prior ethnic and national language mastery. This study investigated how learner profiling and role-playing activities could enhance English-speaking performance and engagement among Indonesian multilingual students. Methods: The research employed a mixed-method approach, studying 197 students from two culturally diverse high schools in East Java and South Sumatra. Data collection included quantitative language proficiency assessments and qualitative student engagement and learning preferences analysis. Findings: The learner profile showed improvements across three dimensions: 21st-century Skills (literacy effectiveness 82.1%), Psychological (learning motivation increase 88.8%), and Linguistic Competence (vocabulary mastery improvement 91.7%). The data shows that 85.4% of students indicated a preference for personalized learning methods over traditional approaches. Conclusion: The findings demonstrate that integrating learner profiling as a diagnostic tool with role-playing as the primary instructional method creates an optimal strategy for English language instruction in classrooms with multilingual students, effectively addressing both foundational skills and practical communication abilities while maintaining high student engagement and reducing learning anxiety. Keywords: multilingual education, foreign language exposure, second language acquisition, teaching English as a Second Language, differentiated learning, personalized learning, learner's profiling, role-playing.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024148